2020
DOI: 10.21203/rs.2.22818/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genome-wide association study and Genomic Prediction of spot blotch disease in wheat (Triticum aestivum L.) using genotyping by sequencing

Abstract: Background Spot blotch caused by Bipolaris sorokiniana is a major constraint in wheat production in tropics and subtropics. There is limited information available on GWAS and study on genomic prediction is completely lacking. To reveal the genetic markers associated with disease resistance, we performed a genome-wide association study (GWAS) for spot blotch disease in 141 spring wheat lines. Results Based on the testing under natural infection in three years at hot spots location in Pusa, India and Jamalpur, B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…The technical support provided by Manish Kumar, Dr. Prashanth N. Suravajhala, and Dr. Raj Kumar Jat is duly acknowledged. This manuscript has been released as a pre-print at ( https://www.researchsquare.com/article/rs-13392/v1 ), [ Tomar et al (2020) Genome-wide association study and genomic prediction of spot blotch disease in wheat ( Triticum aestivum L.). doi: 10.21203/rs.2.22818/v1].…”
mentioning
confidence: 99%
“…The technical support provided by Manish Kumar, Dr. Prashanth N. Suravajhala, and Dr. Raj Kumar Jat is duly acknowledged. This manuscript has been released as a pre-print at ( https://www.researchsquare.com/article/rs-13392/v1 ), [ Tomar et al (2020) Genome-wide association study and genomic prediction of spot blotch disease in wheat ( Triticum aestivum L.). doi: 10.21203/rs.2.22818/v1].…”
mentioning
confidence: 99%
“…Besides enhancing prediction accuracy, GS + GWAS does not require additional data because the same phenotypic and genotypic data set is used, and it can be more accessible to breeders as it does not require extensive knowledge of the underlying genetics of a trait of interest [68]. The benefits of integrating GWAS with GS to further improve the accuracy of GS in wheat are confirmed for rusts [69,70], Septoria tritici blotch [71,72], and yield [73]. Particularly, Daetwyler et al [69] and Rutkoski et al [70] demonstrated the advantage of including markers linked to large to moderate effect genes or loci previously found to affect the traits of interest.…”
Section: Strategies For Improving Gs Prediction Accuracymentioning
confidence: 93%
“…Another 141 spring wheat lines were collected for GWAS on spot blotch resistance. A total of 23 genomic loci were identified, including several stable QTLs on chromosomes 2B, 5B, and 7D, and a novel QTL on chromosome 3D ( Tomar et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%